Electronic commerce, trade and development - Bhatnagar, Pradip (1999)
Recognises electronic commerce as a technological innovation and examines its impact on developing countries in terms of a positive technological shock. Analyzes whether electronic commerce is an 'elist' technology that could widen existing disparities between the urban and rural segments of a backward economy. Describes some unique features of e-commerce that distinguish it from other technological innovations.